2019
DOI: 10.22370/rbmo.2018.53.3.1356
|View full text |Cite
|
Sign up to set email alerts
|

Patrones locales de alimentación del león marino sudamericano <i>Otaria byronia</i>: el caso de Punta Patache, Norte de Chile

Abstract: Mediante análisis de fecas se estudiaron los hábitos alimentarios del león marino sudamericano (Otaria byronia) (LMS) en Punta Patache, norte de Chile durante 2 periodos El Niño (1997/98 y 2009/10). Las muestras fecales (n= 183) fueron colectadas en la lobera de Punta Patache, sur de Iquique (20º48’63’’S). Se identificaron 10 especies de presas neríticas (incluyendo 4 peces, 2 cefalópodos y 3 crustáceos). Los más importantes para el conjunto de ambos períodos fueron en términos de abundancia la anchoveta (Engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(29 reference statements)
0
15
0
2
Order By: Relevance
“…The SASL diet is composed mainly of fish, and to a lesser extent of mollusks and crustaceans (Vaz-Ferreira 1982). There have been only two studies of the sea lion diet in northern Chile using stomach and scat analyses (Sielfeld et al 1997(Sielfeld et al , 2018. With stomach content analysis, Sielfeld et al (1997) determined that the diet of sea lions around Arica (18°34 0 S) was dominated by anchovy (Engraulis ringens), followed to a lesser extent by Patagonian squid (Loligo gahi), cabinza grunt (Isacia conceptionis) and paloma pompano (Trachinotus paitensis).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SASL diet is composed mainly of fish, and to a lesser extent of mollusks and crustaceans (Vaz-Ferreira 1982). There have been only two studies of the sea lion diet in northern Chile using stomach and scat analyses (Sielfeld et al 1997(Sielfeld et al , 2018. With stomach content analysis, Sielfeld et al (1997) determined that the diet of sea lions around Arica (18°34 0 S) was dominated by anchovy (Engraulis ringens), followed to a lesser extent by Patagonian squid (Loligo gahi), cabinza grunt (Isacia conceptionis) and paloma pompano (Trachinotus paitensis).…”
Section: Introductionmentioning
confidence: 99%
“…With stomach content analysis, Sielfeld et al (1997) determined that the diet of sea lions around Arica (18°34 0 S) was dominated by anchovy (Engraulis ringens), followed to a lesser extent by Patagonian squid (Loligo gahi), cabinza grunt (Isacia conceptionis) and paloma pompano (Trachinotus paitensis). However, by means of scat analysis, Sielfeld et al (2018) determined that during two periods of El Niño (1997-1998 and 2009-2010), the sea lion diet south of Iquique (20°48 0 S) was dominated by squat lobster (Pleuroncodes monodon), followed by anchovy and Patagonian squid. These changes in diet are associated with temporal and spatial variations in the availability and abundance of prey caused by climatic phenomena such as El Niño-Southern Oscillation (ENSO; Soto et al 2004Soto et al , 2006Sielfeld et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ω3 fatty acid is a good dietary indicator, which suggests that sea lions from the northern region are feeding on prey rich in DHA, although with great individual variability. Stomach and scat content studies in northern Chile have indicated that the Patagonian squid Loligo gahi, the anchovy Engraulis ringens and the squat lobster Pleuroncodes monodon are the main prey species 54,69 . This coincides with the abundance of DHA in the blubber of sea lions, as cephalopods, crustaceans and fish are rich in DHA, with cephalopods having the highest proportions of DHA within the marine environment 36 .…”
Section: Discussionmentioning
confidence: 99%